A novel quantitative light-induced fluorescence device for monitoring molar-incisor hypomineralization - KARGÜL, BETÜL; YANIKOĞLU, FUNDA (MEDKNOW PUBLICATIONS & MEDIA PVT LTD, 2017)
Background: The FluoreCam system is based on an innovative approach to the quantification of enamel health termed fluorescence enamel imaging (FEI). Enamel is both highly mineralized and semi-translucent. Because of its mineral composition, enamel will fluoresce when exposed to certain light wavelengths. The semi-translucent nature of enamel results in different enamel densities emitting different levels of fluorescence. As a result, with FEI technology, one can measure the density of tooth enamel by measuring its fluorescence when subjected to specific light wavelengths. Purpose: To determine the ability of visual examination and the instrumental procedures of the FluoreCam to monitor molar-incisor hypomineralization (MIH) lesions. Subjects and Methods: This study involved children with MIH at the Department of Paediatric Dentistry, Marmara University. In total, 11 patients with MIH were diagnosed on a visual MIH scale and evaluated with the FluoreCam. The equipment, data processing, and interaction between the equipment and operator were evaluated. Results: Fluorescent images recorded with the custom software, the clinical view, and digital numeric values were evaluated to assess the potential for use of the device in clinical practice. Conclusion: These preliminary data from an ongoing clinical study suggest that measurements with the FluoreCam are useful in monitoring MIH. This technique also provides visual and quantitative feedback to patients.
Keywords: Diagnose; fluorescence imaging; molar-incisor hypomineralisation; OCCLUSAL CARIES DETECTION; IN-VITRO; DENTAL FLUOROSIS; VISUAL EXAMINATION; PERFORMANCE; LESIONS; QUANTIFICATION; PREVALENCE; WATER